Palm diversity of Northern Leyte - Florante, Jehremias M.; Miranda, Allan B.; Viovicente, Ferdinand B.
A survey of palms in the wetlands, lowlands, and highlands of Leyte Province was conducted from November 1998 to February 1999. From the six areas studied, 25 different species of palms were identified. Babatngon had the highest number of species (17) while MacArthur had the least (2). However, Mahaplag which had only 13 species is more diverse than Babatngon. MacArthur is the least diverse in this study The lowland got the highest number of species recorded and the most diverse among the ecosystems studied. The wetland got the least number of species and is least diverse.